HUBUNGAN KECEPATAN LARI 50 METER DAN KELENTURAN PINGGANG DENGAN HASIL LOMPAT JAUH GAYA JONGKOK PADA SISWA SMA MUTIARA 2016/2017 - Husin, Muhammad; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The problem of research in SMA Mutiara Duri, athletic learning has not been implemented perfectly, especially long jump. This is evident from the results of data or direct observation long jump is still less satisfactory (low), especially on the squat style. This study aims to determine the relationship speed of 50 meters and waist flexibility with the results of long jump style squatting on high school students Mutiara Duri Population of this study are all 2nd graders IPS SMA IT Mutiara Duri who followed lesson penjaskes amounted to 20 people. The sample in this study is the total population of 20 people (total sampling). Instruments used to collect data in this study is the speed of running 50 meters, kelenturan waist with back up and long jump. The results obtained in the analysis using simple and multiple moment product correlation. Based on the results of research that has been authors described in the previous chapter, it can be drawn conclusion as follows: From the results obtained running speed is not related to the results of long jump on Pearl students 2016/2017, where the results obtained are rhitung (0.410) of rtabel (0.456). From the results obtained the flexibility of the waist is not related to the long jump results in the students of SMA Mutiara 2016/2017, where the results obtained are rhitung (0.382) <of rtabel (0.456). There is a simultaneous relationship between running speed and waist flexibility with long jump results in Pearl 2016/2017 pupils, where the results obtained are rhitung (0.539)> from rtabel (0.456)Keywords: 50 meter Running Speed, Waist Spatness, Jump Result Far